THE TRANSFORMATION OF THE EGYPTIAN ISLAMISTS : GENUINE VALUE PLURALISM OR DEMOCRATIC WINDOW-DRESSING - Ms. Gillian Kennedy (Journal of Islamic Thought and Civilization, 2011)
During the 1990s, Egyptian society faced an upsurge of violent Islamist attacks by various jihadist inspired groups in which over a thousand people died. In the midst of increasing government suppression and public disgust at these terrorist attacks, other Islamist groups, such as the Muslim Brotherhood (MB) sought to re-orientate their dialogue and strategy towards a more pluralistic rhetoric. Concepts such as human rights, political pluralism and democracy were intermingled with the traditional Islamist narrative. The Egyptian experience, especially in relation to the transformation of the MB is worth discussing in order to address genuineness of this Islamist reorientation towards a new political agenda. Questions relating to positive democratic development and political pluralism need to be ascertained to assess whether the MB‘s transformation is mere democratic window-dressing brought about to gain power, or it is a realisation that a true alternative Egyptian hegemon must adapt to changing times amidst the face of a pluralistic populace. While the Egyptian experience is still being played out, there are indications that suggest the MB is in the midst of organisational change, yet with generational struggles constraining it. This paper shall utilise numerous political theories to produce a theoretical framework for examining power relations in the context of cultural currency and value norms in Egyptian society and how this can harness the ability to build a broad based consensual hegemon throughout Egypt. These emerging issues are replacing old power dynamics based on traditional hierarchical structures, and material capabilities such as military dominance and economic tribalism. Thus, central to this paper is highlighting the methodological framework necessary to explore the democratic credentials within the Egyptian Islamist counter-hegemonic movement.